Safety studies of post-surgical buprenorphine therapy for mice. (April 2015) - Traul, Karl A; Romero, Jennell B; Brayton, Cory; DeTolla, Louis; Forbes-McBean, Nadine; Halquist, Matthew S; Karnes, H Thomas; Sarabia-Estrada, Rachel; Tomlinson, Michael J; Tyler, Betty M; Ye, Xiaobu; Zadnik, Patricia; et al.
The use of appropriate analgesia in laboratory mice may be suboptimal because of concerns about adverse events (AE). Target Animal Safety trials were conducted to determine the safety of an extended-release suspension of buprenorphine. Drug or control suspensions were injected subcutaneously in surgically-treated BALB/c mice anesthetized with ketamine–xylazine to mimic post-operative conditions in which the compound might commonly be administered. Single and repeat five-fold (5×) excesses of the 3.25 mg/kg intended dose were used to provoke potential AE. Trials included prospective measurements of weight changes, blood chemistry, hematology, and histopathology. Clinical and histopathology findings were similar in drug-treated and control mice in a four-day trial using a single 16.25 mg/kg, 5× overdose of the drug. In a 12-day trial, which used a total buprenorphine dose of 48.75 mg/kg, clinical and histopathology values were also similar in control and drug-treated female mice. In the male arm of the repeat-overdose trial, two of eight mice died on the morning of day 12, three days following the third 16.25 mg/kg overdose administration. Histopathology did not reveal a cause of death. In a 14-month trial using a single 3.25 mg/kg dose of the drug, no significant findings identified potential AE. These findings indicate a high tolerance to an extended-release buprenorphine suspension administered post-operatively in mice with appropriate husbandry.